Environmental Factors as Determinants of Health in New Jersey, USA - Blauvelt, Robert P. (Journal of Biology and Life Science, 2021)
There is a well-documented association between socioeconomic factors and community health. While environmental conditions are considered in most public health evaluations, they have the least weighted values of all the metrics measured. The U.S. state of New Jersey has a very robust, long-standing environmental protection program combined with some of the highest educational attainment, employment, and income levels in the country. These conditions may have re-positioned or re-prioritized those societal factors that traditionally dominate health outcomes, placing greater emphasis on environmental factors. This paper seeks to evaluate whether in New Jersey at the county level the long-established connection between health status and environmental quality conditions needs to be re-defined. Because of its high per capita income, well-educated population, and strong industrial and service sector employment base, New Jersey residents are fairly healthy, and New Jersey is generally placed within the top ten healthiest places to live in the United States. Thus, this state is well positioned to assess the relative importance that releases to air, water, and soil may play in determining health outcomes. This is due to the state’s long history of significant pollution of its air, water, and soil coupled with a strong, effective regulatory program that slowly is achieving meaningful improvements to environmental quality.